Ripening associated physico-biochemical changes in red fleshed organic dragon fruit of Mizoram, India - Lalduhsangi, R C; Mandal, Debashis (Journal of Postharvest Technology, 2023)
A study was conducted with red fleshed organically grown dragon fruit (Hylocereus polyrhizus) at north-eastern Himalayan region of Mizoram, India; for evaluating ripening associated physico-biochemical changes to select optimum mature fruits for local as well as distant market. Fruits were collected from organic dragon fruit farm of Ailawg village, Mamit district of Mizoram. Data analyses revealed that fruit growth and development was comparatively slow for the first three weeks after fruit set, followed by rapid growth of one week and again a slow growth for final week. Fruits at 35 days after fruit set (DAFS) had maximum size in terms of fruit length (77.25±4.26 mm), diameter (70.25±2.68 mm) and volume (203.25±2.86 cc) with high fruit weight (211.80±6.91 g), pulp recovery (56.35±2.44%) and pulp: peel ratio (1.11±0.05). Besides, fruits at this stage had highest TSS:acid ratio (99.22±7.88) and ascorbic acid (24.79±2.06 mg100g-1) along with good pulp and peel colour as determined by anthocyanin content (pulp: 10.34±1.38 mg100g-1, peel: 5.67±1.05 mg100g-1). However, these values were quite good after 28 DAFS as the fruits were turning colour. Therefore, it may be concluded that organic red fleshed dragon fruit has to be harvested 35 days after fruit set for local market while it will be good to harvest at 28 DAFS for distant market.